Analysis of the Effect of Direct Cash Assistance from Village Funds on Increasing Community Welfare - Hardi; Sab'ul Masani (Saniya Institute, 2024)
This research examines the involvement of the East Gereneng Village community in managing Village Funds, especially the BLT-DD program. Even though there are participation mechanisms such as village meetings, community understanding of finance and supervision is still limited. Transparency in the use of funds is also a main issue. The research results show that people want more frequent financial reports and easier access to information. To increase management effectiveness, several suggestions were put forward, namely: intensive training for the community, strengthening transparency and accountability, expanding financial literacy programs, and integrating traditional knowledge with modern financial concepts. In conclusion, community participation and financial literacy are the keys to successful Village Fund management. By improving these two aspects, it is hoped that Village Funds can be utilized optimally for community welfare.